092 Cryolipolysis-induced radial mononeuropathy. (23rd August 2021) - Harinesan, Nimalan; Wijesinghe, Rajiv; Hayes, Michael; Triplett, James D
Abstract : Objectives: To report an association between cryolipolysis or 'fat-freezing' in the upper arm and development of an acute radial neuropathy likely secondary to a combination of thermal and pressure effects. Results: A 31-year-old female presented with an acute right wrist drop that occurred following a cryolipolysis procedure to the upper right arm. Paraesthesia and numbness occurred towards the end of a 40-minute cryolipolysis procedure, with weakness reported within 24 hours. Examination of the arm 1 week following symptom onset revealed a significant ecchymosis at application site of the fat freezing device. In addition, there was severe weakness of right elbow, wrist and finger extension with an anaesthetic patch over the anatomical snuff box. Ultrasonography showed fascicular oedema of the radial nerve in the upper arm. Nerve conduction studies confirmed an acute axonotmetic radial neuropathy at the spiral groove. The patient was referred for hand therapy and at 4 months regained most of the function in her hand, with some mild persistent sensory impairment. Conclusions: Cryolipolysis is a cosmetic treatment that aims to locally reduce subcutaneous fat. The procedure is performed using a vacuum applicator to cool the selected area to temperatures as low as -9 degrees Celsius. Peripheral neuropathies following the procedure have been rarely described 1 but, to our knowledge, this is the first report of an acute neuropathy developing during the procedure. The causative mechanisms of cryolipolysis-induced nerve injury in this case were likely due to nerve compression related to local oedema and thermal effect on the radial nerve. Reference: Jong Gyu Baek, Jung A Park, Jung Im Seok. Radial neuropathy after cryolipolysis. Journal of the Korean Neurological Association 2017;35 :1, 30–32.